Deep-Sea Biofilms, Historic Shipwreck Preservation and the Deepwater Horizon Spill - Mugge, Rachel L.; Brock, Melissa L.; Salerno, Jennifer L.; Damour, Melanie; Church, Robert A.; Lee, Jason S.; Hamdan, Leila J. (Frontiers in Marine Science, 2019)
Exposure to oil from the Deepwater Horizon spill may have lasting impacts on preservation of historic shipwrecks in the Gulf of Mexico. Submerged steel structures, including shipwrecks, serve as artificial reefs and become hotspots of biodiversity in the deep-sea. Marine biofilms on submerged structures support settlement of micro- and macrobiota and may enhance and protect against corrosion. Disruptions in the local environment, including oil spills, may impact the role that biofilms play in reef preservation. To determine how the Deepwater Horizon spill potentially impacted shipwreck biofilms and the functional roles of the biofilm microbiome, experiments containing carbon steels disks (CSDs) were placed at five historic shipwreck sites located within, and external to the benthic footprint of the Deepwater Horizon spill. The CSDs were incubated for 16 weeks to enable colonization by biofilm-forming microorganisms and to provide time for in situ corrosion to occur. Biofilms from the CSDs, as well as sediment and water microbiomes, were collected and analyzed by 16S rRNA amplicon gene sequencing to describe community composition and determine the source of taxa colonizing biofilms. Biofilm metagenomes were sequenced to compare differential gene abundances at spill-impacted and reference sites. Biofilms were dominated by Zeta-, Alpha-, Epsilon and Gammaproteobacteria. Sequences affiliated with the Mariprofundus and Sulfurimonas genera were prolific, and Roseobacter, and Colwellia genera were also abundant. Analysis of 16S rRNA sequences from sediment, water, and biofilms revealed sediment to be the main known source of taxa to biofilms at impacted sites. Differential gene abundance analysis revealed the two-component response regulator CreC, a gene involved in environmental stress response, to be elevated at reference sites compared to impacted sites within the spill plume fallout area on the seafloor. Genes for chemotaxis, motility, and alcohol dehydrogenases were differentially abundant at reference vs. impacted sites. Metal loss on CSDs was elevated at sites within the spill fallout plume. Time series images reveal that metal loss at a heavily impacted site, the German Submarine U-166, has accelerated since the spill in 2010. This study provides evidence that spill residues on the seafloor may impact biofilm communities and the preservation of historic steel shipwrecks.